Global Forestry Areas, Deforestation and Mental Health: A Worldwide Ecological Study - Alice Bolton (BJPsych Open)
Aims: Forests are important for planetary and human health, but deforestation is increasing. Poor mental health is increasingly affecting the world’s population. This study aims to investigate the association between forestry area, deforestation and mental health, at country level, worldwide.